Octreotide and pasireotide effects on medullary thyroid carcinoma (MTC) cells growth, migration and invasion. (15th January 2021) - Giardino, E.; Catalano, R.; Mangili, F.; Barbieri, A.M.; Treppiedi, D.; Elli, F.M.; Dolci, A.; Contarino, A.; Spada, A.; Arosio, M.; Mantovani, G.; Peverelli, E.
Abstract: Medullary thyroid carcinoma (MTC) is a rare neuroendocrine neoplasm of the parafollicular thyroid C cells. Although somatostatin receptors are expressed by MTCs, treatment with octreotide has shown poor efficacy, whereas recently pasireotide has demonstrated antiproliferative effects in persistent postoperative MTCs. Aim of this study was to test the effects of octreotide and pasireotide on MTC cells proliferation, cell cycle proteins expression, MAPK activation, apoptosis, calcitonin secretion, migration and invasion in TT cell line as well as in primary MTC cultured cells. Our results showed that both octreotide and pasireotide reduced TT cell proliferation (−35.2 ± 12.1%, p < 0.001, and −25.3 ± 24.8%, p < 0.05, at 10 −8 M, respectively), with concomitant inhibition of ERK phosphorylation and cyclin D1 expression. This cytostatic effect was accompanied by a proapoptotic action, with an increase of caspase3/7 activity of 1.5-fold. Moreover, both octreotide and pasireotide inhibited cell migration (−50.9 ± 11.3%, p < 0.01, and −40.5 ± 17%, p < 0.05, respectively) and invasion (−61.3 ± 35.1%, p < 0.05, and −49.7 ± 18%, p < 0.01, respectively). No effect was observed on calcitonin secretion. We then tried to extend these observations to primary cultures (n = 5). Octreotide and/or pasireotide were effective in reducing cells proliferation in 3 out of 5 tumors, and to induce cell apoptosis in 1 out of 3 MTCs. Both octreotide and pasireotide were able to reduce cell migration in all MTC tested. SST2, SST3 and SST5 were expressed in all MTC, with a tendency to increased expression of SST2 in RET mutated vs wild type MTCs. In agreement, inhibition of mutated RET in TT cells reduced SST2 expression. In conclusion, we demonstrated that octreotide and pasireotide inhibited cell proliferation and invasiveness in a subset of MTC, supporting their potential use in the control of tumor growth. Highlights: Octreotide and pasireotide reduced with similar efficacy TT cell growth. Only a subset of primary MTC cells were responsive to octreotide and pasireotide. Octreotide and pasireotide exerted cytostatic and cytotoxic effects in MTC cells. We first showed antiinvasive properties of octreotide and pasireotide in MTC cells. Oncogenic mutant RET induced an increase of SST2 expression.